The study of transcarotid artery revascularization under local versus general anesthesia with results from the Society for Vascular Surgery Vascular Quality Initiative. (December 2020) - Mukherjee, Dipankar; Collins, Devon T; Liu, Chang; Ha, Neul; Jim, Jeffrey
Objective: The primary purpose of this study was to examine any potential difference in clinical outcomes between transcarotid artery revascularization performed under local anesthesia compared with general anesthesia by utilizing a large national database. Methods: The primary outcome of the study was a composite endpoint of postoperative in-hospital stroke, myocardial infarction and mortality following transcarotid artery revascularization for the index procedure. Secondary outcomes included a composite outcome of postoperative in-hospital stroke, transient ischemic attack, myocardial infarction and mortality along with several subsets of its components and each individual component, flow reversal time (min), radiation dose (GY/cm 2 ), contrast volume utilized (mL), total procedure time (min), extended total length of stay (>1 day) and extended postoperative length of stay (>1 day). Statistical analyses employed both descriptive measures to characterize the study population and analytic measures such as multivariable mixed-effect linear and logistic regressions using both unmatched and propensity-score matched cohorts. Results: A total of 2609 patients undergoing transcarotid artery revascularization between the years 2016 and 2018 in the US were identified, with 82.3% performed under general anesthesia and 17.7% under local anesthesia. The primary composite outcome was observed in 2.3% of general anesthesia patients versus 2.6% of local anesthesia patients ( p = 0.808). The rate of postoperative transient ischemic attack and/or myocardial infarction was 1.6% with general anesthesia versus 1.1% with local anesthesia ( p = 0.511). For adjusted regression analysis, general anesthesia and local anesthesia were comparable in terms of primary outcome (OR: 0.72; 95% CI: 0.27–1.93, p = 0.515). As for the secondary outcomes, no significant differences were found except for contrast, where the results demonstrated significantly less need for contrast with procedures performed under general anesthesia (coefficient: 4.94; 95% CI: 1.34–8.54, p = 0.007). A trend towards significance was observed for lower rate of postoperative transient ischemic attack and/or myocardial infarction (OR: 0.33; 95% CI: 0.09–1.18, p = 0.088) and lower flow reversal time under local anesthesia (coefficient: –0.94: 95% CI: –2.1–0.22, p = 0.111). Conclusions: Excellent outcomes from transcarotid artery revascularization for carotid stenosis were observed in the VQI database between the years 2016 and 2018, under both local anesthesia and general anesthesia. The data demonstrate the choice of anesthesia for transcarotid artery revascularization does not appear to have any effect on clinical outcomes. Surgical teams should perform transcarotid artery revascularization under the anesthesia type they are most comfortable with.